Rancang Bangun Aplikasi Tracer Study Berbasis Android di Politeknik Pelayaran Sulawesi Utara - Irawan, Santun; Silalahi, Aliong; Pongoh, Frisca Mareyta; Frastika, Yustiani; Ansar, Azhar Ariansyah (LPPM UNIKA Santo Thomas Medan, 2024)
Advancements in information technology have simplified various aspects of human life, including in the education sector. One important tool for monitoring the effectiveness of higher education is a tracer study information system, which allows educational institutions to gather data on alumni and their contributions to the workforce. Politeknik Pelayaran Sulawesi Utara (PPSU), as a higher education institution under the Ministry of Transportation, faces challenges in managing alumni data that are dispersed across various regions in Indonesia. Therefore, this study aims to design and develop an Android-based tracer study application to streamline the management of alumni data more efficiently and accurately. The research methodology employed is the waterfall model, which includes the stages of planning, analysis, design, implementation, and testing. The findings of this study indicate that the developed Android-based tracer study application can assist in managing alumni data more efficiently, allowing administrators to obtain real-time information from anywhere. This application also provides convenience for alumni to update their information while offering constructive feedback to improve the quality of education at PPSU. Based on the test results, the application is deemed feasible and effective for use in managing alumni data. This research is expected to serve as a reference for the development of similar systems at other higher education institutions and contribute to the improvement of higher education quality in Indonesia.